Preclinical Investigation of Radiopharmaceuticals: An Accurate and Multidisciplinary Approach - Urbano, Nicoletta; Scimeca, Manuel; Bonanno, Elena; Schillaci, Orazio (Current Radiopharmaceuticals, 2022)
Background: The development of less expensive and pivotal methodologies capable of supporting the researchers in the radiopharmaceutical pre-clinical investigations could provide a crucial incentive for conducting biomedical research involved in the realization of tailored target therapies. Objective: The aim of this pilot study was to evaluate the capability of a digital autoradiography system equipped with a laser scanning device to perform [18F] choline biodistribution evaluation in a xenograft mouse model of prostate cancer. Methods: PC3 prostate cancer cells were used to develop NOD/SCID mice xenografts. The biodistribution of the radiopharmaceuticals was evaluated at 30, 60, and 120 min after injecting in excised organs by using a digital autoradiography system equipped with a super-resolution laser screen. Histological and immunohistochemical analyses were performed to correlate the [18F] choline uptake with morphological and molecular tumours characteristics. Results: The reported data clearly indicate the possibility of performing accurate biodistribution studies using the digital autoradiographic system equipped with a super-resolution screen. Specifically, a significant increase in the [18F] choline inhibitor uptake in PC3 tumours compared to heart, bowel, liver, and kidney at both 30 and 60 min was observed. More importantly, the digital autoradiographic system showed signal uptake almost exclusively in the PC3 tumors at 60 min post-injection. Noteworthy, immunohistochemical analysis demonstrated a strong overlapping between the [18F] choline uptake and the proliferation index (Ki67 expression). Conclusion: The use of an autoradiography system in pre-clinical investigations could shed new light on the molecular mechanisms that orchestrate the tissues damage induced by therapeutical radiopharmaceuticals.
Keywords: micro-PET